Intervensi Pencegahan Perilaku Bunuh Diri pada Remaja Berbasis Aplikasi dalam Meningkatkan Efektivitas Penanganan Kesehatan Mental - Priambodo, Rian; Fitryasari, Rizki; Tristiana, Rr Dian (Journal of Telenursing (JOTING), 2024)
This research aims to develop a suicide prevention intervention for adolescents by utilizing technology to reach adolescents with suicidal behavior effectively and efficiently. The method used was a literature review with articles originating from the Scopus, Web of Science, Wiley Online, and Science Direct databases, to search for keywords using the Medical Subject Headings (MeSH) system related to relevant articles in this research. The research results resulted in an initial 354 articles. Articles were selected based on publications in the last 5 years and did not include literature reviews or systematic reviews, screening 187 articles. The final results of the 15 articles synthesized showed that there was effectiveness of screening interventions, education, DBT (dialectical behavioral therapy) skills, and help seeking in adolescents with suicidal behavior. The conclusion of this research is that suicide prevention interventions for teenagers by utilizing application technology on smartphones have proven to be effective and efficient in reaching and helping teenagers with suicidal ideation. Keywords: Application, Suicide Prevention, Suicide Intervention, Teenagers